Method on Specifying Consistency Rules among Different Aspect Models, expressed in UML - Dubauskaite, R.; Vasilecas, O. (Elektronika ir Elektrotechnika, 2013)
Unified Modelling Language (UML) allows modelling different aspects of information system (IS) through the various diagrams it supports. Expression of an IS through class, state, sequence and other models is related to the problem of checking consistency among different aspect UML models. Consistency means that two or more overlapping elements of different aspect models match each other. Approaches of checking UML models are based on rules. Most of consistency rules are ambiguous, do not conform OMG UML metamodel and sometimes are meaningless. In order to improve consistency of different aspect models, the approach of checking consistency is proposed, paying a special attention on requirements of consistency rules. Example of consistency rule and experiments are presented. Ill. 2, bibl. 24, tabl. 3 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.19.3.2058